44 Local Versus General Anaesthesia in Transcatheter Aortic Valve Replacement: A Tertiary Centre Experience. (3rd June 2016) - Jabbar, Avais; Mohammed, Ashfaq; Das, Rajiv; Zaman, Azfar; Edwards, Richard
Abstract : Introduction: Transcatheter aortic valve replacement (TAVR) is an option for patients with severe aortic stenosis who are declined conventional surgery due to comorbidities. TAVR is conventionally performed under general anaesthesia (GA) allowing intraoperative TOE imaging. We present our experience in patients having the procedure under local anaesthesia (LA). Aims: To assess safety and length of hospital stay in patients who have a TAVI under GA compared to LA. Methods: We retrospectively assessed all the transfemoral TAVR procedures conducted at our centre from 01/03/2011 when we started performing the procedure under LA. Of 221 patients, 145 had the procedure under GA and 71 under LA. In the GA group, the devices used were Sapien XT 95%, Sapien 3 (S3) 2%, Direct Flow Medical (DFM) 5%. In the LA group the devices used where S3 64% XT 8% and DFM 28%. Results: Both groups were similar with respect to age (80.2 vs 80.9), comorbidities, Euro Score (18.5 vs 18.8) and the severity of the aortic stenosis (AVA 0.66 vs 0.67cm 2, mean/peak gradient 45.5 vs 44.2, 77.1 vs 74.5mmHg). Tranoesophageal echocardiography for aortic annular measurements was used in 79.7% of GA patients whereas CT was used in 100% of LA patients. The procedure time was significantly shorter in the LA group measured from time in room to skin closure (108 mins v 143 mins; p < 0.001). Skin open to skin closure time were the same in both groups (78 mins v 79.4 mins; p = 0.57). There was no difference in 30 day: aortic regurgitation>mild (2.06% in GA and 2.82% in LA; p = 0.744), need for permanent pacing (2.32% in GA and 1.4% in LA; P = 0.617), and cerebrovascular accidents (1.4% and 1.4%, p = 0.986). The 30 day survival was significantly different (96.5% in GA and 100% in LA; P = 0.023) as was the mean number of days in hospital (7.1 in GA and 4.6 in LA; P < 0.001). No emergency conversions to GA were performed in the LA group, although there were two planned intubations, one to convert to the transaortic approach and one to perform a femoral artery repair. Conclusions: Performing a TAVR under LA is at least as safe as GA. In addition there is a reduced procedural time and length of hospital stay. LA is a safe and cost effective alternative to GA.